Impact Of Magnetic Field On Natural Convective Flow Of A Micropolar Fluid Between Two Porous Vertical Walls (International Journal of Food and Nutritional Sciences, 2022)
Mathematical analysis of an unsteady boundary layer flow of an incompressible micro-polar fluid under uniform magnetic field and motion takes place due to the buoyancy force between porous vertical walls along heat source has been carried out. The governing unsteady boundary layer momentum, angular momentum and energy equations of micro-polar fluid are nondimensionilzed and solved numerically by using finite difference method. The effect of magnetic parameter, porous permeability, vortex viscosity parameter, Prandtl number and material parameter on velocity, micro-rotation and temperature profiles is discussed numerically.